Lail Adventure : Perancangan Antarmuka Game Edukasi Yang Ramah Pengguna Menggunakan Wireframe Dan Prototype - Azzahry Dwi Pramudio Pramudio (Jurnal Repositor, 2026)
The development of the Islamic educational game interface "Lail Adventure" focuses on user-friendly design within the Muhammadiyah-themed platformer genre. The main issues identified include the limited options for educational games with a Muhammadiyah theme and the need to create an attractive and intuitive interface design. The methods used involve wireframing for initial sketches and prototyping for an interactive model close to the final product. Wireframing offers quick visualization of ideas and early error detection, while prototyping provides a detailed overview of user interaction but requires more time and resources. Testing conducted using the System Usability Scale showed that the combination of these methods resulted in an adjective rating of "good," a grade scale rating of B, and an "acceptable" score in the acceptability range. These findings highlight the importance of a user-friendly interface in enhancing the effectiveness of learning through educational games.